The corporate income tax gap in South Africa: A top-down approach - Ada Jansen; Winile Ngobeni; Alexius Sithole; Wynnona Steyn (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
A key objective of many governments is to improve tax revenue mobilization. One way to achieve this is by improving tax compliance. This requires accurate knowledge of the tax gap, i.e. the difference between what should be paid and what is actually paid. Until now, tax gaps have been primarily estimated in developed countries, and very little is known about tax gaps in developing countries. Information about these gaps can help policy makers make appropriate revenue mobilization strategies. This paper uses a top-down approach to estimate the tax gap in corporate income tax in South Africa. It uses national accounts statistics and tax administrative data to estimate the gap in the non-financial corporate sector, i.e. the difference between potential and actual corporate income tax under current tax legislation. The overall gap is estimated at approximately 11 per cent of the potential tax base or 2 per cent of GDP over the period 2015 to 2017.
Keywords: H2; H25; H26; 330; corporate income tax; tax compliance; tax gap; top-down approach